An instrumented reinforced earth wall - Ali, F.; Hai, L.C. (Academic Journals, 2010)
Reinforced earth wall system has become very popular because of its aesthetic value and ease of construction. In order to optimize the design, it is important to understand its behavior during and after construction. This can be achieved either through field instrumentation or numerical simulation. In this paper, field instrumentation work carried out on a reinforced earth wall is described with the objective of capturing the essential behaviour of the wall during and after construction. Two different wall conditions were considered, that is, in the first case, the wall is allowed to move laterally and in the other case, the wall is not flexible in transverse direction. Based on the observations made, it can be concluded that the locus of maximum tension is a vertical line offset approximately 0.35 H away from the facing. For lateral pressure, it is seen that the curve for the flexible facing follows similar trend as the curve for the rigid facing except that the horizontal pressure at the flexible facing is generally slightly lower. Lastly, the connection ratio at rigid facing is generally higher than the connection ratio at the flexible facing.